The effects of mesenchymal stem cells treated with estrogen on neutrophil cells functions - Nahideh Afzal ahangran; Zahra Nekoei; Nouroz Deliraj; Seyyed Meisam Abtahi Foroushani (Fasa University of Medical Sciences, 2017)
Background & Objectives: The regulatory role of the mesenchymal stem cells on the cells of immune system such as neutrophil has been investigated in several studies. On the other hand, estrogen hormone is one kind of immunomodulatory agents. This study was designed to investigate the effect of mesenchymal cells treated with estrogen on the neutrophil function. Materials & Methods: Having isolated the mesenchymal stem cells from bone marrow of rats, the researchers treated the cells with 10 or 20 nM concentrations of estrogen for 72 hours. In the next stage, the MSC cells were co-cultured with neutrophil cells and incubated for 1 hour. Then, the neutrophil functions were assessed (P<0/05). Results: The results of the study clearly showed that the percentage of phagocytosis and the respiratory burst in co-cultured neutrophil with mesenchymal stem cells treated with estrogen had increased compared to that of the control group. Moreover, the rate of apoptosis in neutrophils treated with estrogen significantly decreased in both estrogen concentrations compared to that of the control group (P<0/05). Conclusion: It seems that estrogen can modify the interaction of the mesenchymal stem cells and neutrophil.